SOME MEANINGFUL AND FUN ACTIVITIES FOR TEACHING ENGLISH TO YOUNG LEARNERS - Janita Norena (HOLISTICS, 2020)
Teaching English to young learners (TEYL) is very important to do. Many benefits can be got since young learners have much potential to be developed. However, Teaching English to young learners is not easy. Most teachers feel very frustrated because they do not have experiences and knowledge how to cope with the young learners. Actually TEYL can be both a rewarding and a demanding experience if teachers do appropriate activities in the classroom. To make this experience easier, more enjoyable and meaningful for both, teachers must identify what learning a language in school requires for young children. Subsequently, teachers need to use the basic principles of teaching young learners as the bases of selecting appropriate activities as offers to the young learners. Therefore, this paper discusses young learners’ needs in learning English and provides some meaningful and fun activities as choices to be implemented.